Longitudinal analysis of stressors, stress, coping and coping effectiveness in elite esports athletes - Poulus, D. R.; Coulter, T. J.; Trotter, M. G.; Polman, R. (Psychology of Sport and Exercise, 2022)
Objective The current study aimed to longitudinally examine the stressors, stress appraisal, coping, and coping effectiveness experienced by elite esports athletes.